Synanthropisation of coastal vegetation in southern Spain - Enríquez-de-Salamanca, Álvaro (Mediterranean Botany, 2023)
Coastal dunes have high ecological value, but are often damaged or overexploited by beach tourism. The main problems for the vegetation of this ecosystem are the physical destruction and the synanthropisation, the latter due to the colonisation of both alien and apophyte species, favoured by human action. This study analyses the degree of synanthropisation of the vegetation of a stretch of coastline in southern Spain, by systematically surveying the flora present in six biotopes: beach, foredune, mid-dune, back-dune, creek and rocky area. The percentage of synanthropic species was 51%, of which 33% are apophytes, mainly ruderal species and weeds, and 18% are alien species, mostly from gardens adjacent to the coastal zone. The degree of synanthropisation varies by biotope, ranging from zero on the beach to 63% on the back-dune, with a marked increase from the beach inland. Richness and diversity is highest in biotopes with higher synanthropisation, but at the cost of lower naturalness. Measures need to be taken to protect coastal vegetation, both from destruction and synanthropisation.